The Effect of Work Motivation, Compensation on Performance Employees at The Village Service - Isna Yudistia; Nina Nurani (Politeknik Siber Cerdika Internasional, 2023)
Factors that influence the achievement of performance are factors of work motivation and compensation. Motivation is formed from an employee's attitude in dealing with work situations. Motivation is a condition that drives self-directed employees to achieve organizational goals. A mental attitude encourages employees to achieve maximum work performance, so they can achieve maximum performance if they have high work motivation. The research objective was to determine the effect of work motivation on employee performance and compensation on employee performance in the Cisaranten Bina Harapan sub-district. The sampling technique uses saturated sampling, where all population members are used as samples. The sample used is 36 respondents. The data collection method was carried out by distributing questionnaires and data analysis using SPSS. This study shows that work motivation has a positive and significant effect on employee performance, and compensation has a positive and significant effect on employee performance in Cisaranten Bina Harapan village.